2006
DOI: 10.4049/jimmunol.176.3.1759
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Characterization and Antibacterial Function of Persisting Granulocytes in Leukemic Patients Receiving Pulse Cytosine Arabinoside-Consolidation Chemotherapy on Days 1, 3, and 5

Abstract: High-dose cytosine arabinoside (HiDAC) and intermediate-dose cytosine arabinoside (IDAC) have been introduced as effective and safe consolidation chemotherapy in acute myeloid leukemia, with relatively low rates of life-threatening infections despite the high total dose of the cytostatic drug. To explore the biological background of low toxicity, we examined the numbers, immunophenotype, and functional properties of granulocytes in patients with acute myeloid leukemia receiving HiDAC or IDAC. Interestingly, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…Analysis of the Characteristics of Sugars and Glycosides in I. hispidus Grown on Five Different Trees Species. Recent investigations have revealed that sugars and glycosides are important bioactive components in mushrooms, such as G. lucidum polysaccharides having antibacterial, 17 antitumor, 18 immunomodulatory, 19 and inflammation effects. 20 In this study, 19 sugars and 42 glycoside metabolites were identified in I. hispidus grown on five different tree species (Table 2).…”
Section: ■ Resultsmentioning
confidence: 99%
“…Analysis of the Characteristics of Sugars and Glycosides in I. hispidus Grown on Five Different Trees Species. Recent investigations have revealed that sugars and glycosides are important bioactive components in mushrooms, such as G. lucidum polysaccharides having antibacterial, 17 antitumor, 18 immunomodulatory, 19 and inflammation effects. 20 In this study, 19 sugars and 42 glycoside metabolites were identified in I. hispidus grown on five different tree species (Table 2).…”
Section: ■ Resultsmentioning
confidence: 99%
“…days 1-7) and etoposide (100 mg/m 2 i.v., days 1-5) and 3 or 4 cycles of consolidation chemotherapy with high or intermediate dose ARA-C (i.e. 2x 3g/m 2 , days 1,3,5 or 2x 1g/m 2 , days 1,3,5, respectively) [4850]. After achieving hematologic remission, patients were treated with HDC (0.5 mg) plus recombinant IL-2 (16400 IU/Kg) twice-daily s.c. for 21 days per cycle, according to an established protocol [18].…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, members of the LBC ONC and the Medical University of Vienna conducted a clinical trial exploring the clinical tolerability and efficacy of a special form of intensified consolidation after remission induction in older patients with AML [ 92 ]. The consolidation regimen was developed on the basis of a previous study showing that intermediate ARA‑C (cytosine arabinoside) is not only a highly effective but also a less toxic and extremely well-tolerated type of consolidation chemotherapy [ 93 , 94 ]. In the trial conducted recently, AML patients ≥ 60 years in complete remission after induction therapy received fludarabine and ARA-C in consolidation cycle 1 and intermediate-dose ARA-C (IDAC) in cycles 2 through 4.…”
Section: Clinical Translation Of Lsc Concepts: Examples and Status 20mentioning
confidence: 99%